Pengaruh Film Animasi Bluey Terhadap Ketrampilan Berkomunikasi Anak Usia Dini - Hiru Muhammad (Departement of Mathematics Education, 2024)
This study aimed to investigate the impact of the popular animated series, Bluey, on the language development of young children. A quantitative survey design was employed to analyze the correlation between the intensity of Bluey viewing and children's language skills. The sample consisted of 30 children aged 3-6 years from Taman Baca Amalia. Results showed a significant positive correlation between the intensity of Bluey viewing and children's language abilities, including vocabulary, syntax, and narrative skills. The study also found that children who watched Bluey more frequently exhibited higher levels of imitation of Bluey's language patterns. These findings suggest that high-quality animated programs like Bluey can have a significant educational value, particularly in terms of language development. This study contributes to the understanding of the role of media in early childhood education and highlights the potential of integrating entertainment elements into language learning strategies.